2016
DOI: 10.33158/asb.2016v2i1p11
|View full text |Cite
|
Sign up to set email alerts
|

Productivity potential and coconut waste quality for biorefining

Abstract: The use of biomass as an energy source has increased as far as it aims at providing sustainable energy alternatives and considerable reduction in agro-industrial and urban solid waste. Techniques employed for different types of biomass by biorefineries intend not only to add value to a bioproduct, but also to reduce environmental impact caused by industrial and agricultural residues. The coconut fruit shell residue, largely consumed in coastal regions, rich in fiber, lignin, cellulose and hemicelluloses, may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…The processing of coconuts for export includes the removal of the husks, most often discarded unsustainably. In a study conducted in Brazil, it was found that 125 units of coconut material occupies 1m 3 volume, which has led to land management and landfill issues (Becker et al, 2016). This study found that the average energy potential of the husk of a single coconut was 7.63MJ.…”
Section: Energy Analyses Of the Coconut Biomassmentioning
confidence: 84%
See 3 more Smart Citations
“…The processing of coconuts for export includes the removal of the husks, most often discarded unsustainably. In a study conducted in Brazil, it was found that 125 units of coconut material occupies 1m 3 volume, which has led to land management and landfill issues (Becker et al, 2016). This study found that the average energy potential of the husk of a single coconut was 7.63MJ.…”
Section: Energy Analyses Of the Coconut Biomassmentioning
confidence: 84%
“…In Guyana, agricultural biomasses, more specifically coconut waste (shell and husk), are abundant and discarded inappropriately, resulting in environmental pollution and social issues (Hoque and Bhattacharya 2001). Coconut (Cocos nucifera) stemming from the family of Arecaceae (palmae) thrives well in areas with altitudes lower than 1000meters (m) and around coastal regions with temperatures of 23-34C (Becker et al, 2016). The plant, usually grouped as tall and dwarf palms, produces the coconut fruit which consists of three layers; exocarp (outer skin), mesocarp (husky fibers) and endocarp (hard brown shell).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coconut is being produced as one of the important foods and oil sources around the world. More than 20 million tons of coconut wastes are directly or indirectly being dumped in our ecosystem every year [4]. Being one of the top producers of coconut, the estimated wastage of coconut agriculture and processing industries in India is very high.…”
Section: Introductionmentioning
confidence: 99%